Perbedaan Status Gizi Pada Bayi Berumur 4-6 Bulan YangDiberikan Asi Eksklusif Dengan Asi Non Eksklusif - Karuniawati, Mira Candra (2016)
The Difference in Nutritional Status between Infants Aged 4-6 Months on Exclusive Breastfeeding and Non-Exclusive Breastfeeding Mira Candra Karuniawati, M.Shoim Dasuki, Anika Candrasari Medical Faculty of Muhammadiyah Surakarta University Background: The coverage of exclusive breastfeeding in Indonesia is only 42%, that figure is below the WHO target of at least 50% coverage of exclusive breastfeeding for infants aged 0-6 months. And found 19.6% among children under the age of five are found malnourished. Toddler is the golden period in a child's life that characterized by growth and development rapidly as well as vulnareble of malnourished. Breastfeeding helps the physical growth and mental and intellectual development of infants, therefore more attention should be paid in order to realize the benefits. Objective: To explore the difference in nutritional status between infants aged 4-6 months who are exclusively breastfed and those who are not exclusively breastfed. Methods: This study used an analytical observational research method with crosssectional approach. 80 infants aged 4-6 months were drawn by purposive sampling technique. Chi-square test was employed as the statistical test. Results: The result showed p-value = 0.000 (p< 0.05), which means there is significant difference between the nutritional status of infants aged 4-6 months who are exclusively breastfed and of those who are not exclusively breastfed. It was found that 40 infants who were exclusively breastfed had better nutritional status than those not exclusively breastfed. Poor nutritional status was more common in non-exclusive breastfeeding infant group. Conclusion: There is a difference in nutritional status between infants aged 4-6 months who are exclusively breastfed and those who are not exclusively breastfed. Keywords: exclusive breastfeeding, non-exclusive breastfeeding, nutritional status